2016
DOI: 10.1038/srep30717
|View full text |Cite
|
Sign up to set email alerts
|

Novel combination of sorafenib and biochanin-A synergistically enhances the anti-proliferative and pro-apoptotic effects on hepatocellular carcinoma cells

Abstract: Sorafenib (SOR) is the first-line treatment for hepatocellular carcinoma (HCC). However, its use is hindered by the recently expressed safety concerns. One approach for reducing SOR toxicity is to use lower doses in combination with other less toxic agents. Biochanin-A (Bio-A), a promising isoflavone, showed selective toxicity to liver cancer cells. We postulated that combining SOR and Bio-A could be synergistically toxic towards HCC cells. We further evaluated the underlying mechanism. Cytotoxicity assay was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 50 publications
2
27
0
Order By: Relevance
“…Moreover, biochanin A may improve lipid profile as a peroxisome proliferator-activated receptor gamma (PPARγ) agonist and provide beneficial effects on metabolic syndrome such as hyperglycaemia (Wang et al, 2014 ; Park et al, 2016 ). It has been reported that biochanin A may be useful in the prevention and treatment of breast cancer, prostate cancer and hepatocellular carcinoma (Sun et al, 1998 ; Khan et al, 2011 ; Chen J. et al, 2015 ; Youssef et al, 2016 ). In addition, biochanin A was shown to exert neuroprotective effect in neurodegenerative diseases via inhibiting microglia activation or attenuating L-glutamate cytotoxicity (Chen et al, 2007 ; Tan et al, 2013 ; Wang J. et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, biochanin A may improve lipid profile as a peroxisome proliferator-activated receptor gamma (PPARγ) agonist and provide beneficial effects on metabolic syndrome such as hyperglycaemia (Wang et al, 2014 ; Park et al, 2016 ). It has been reported that biochanin A may be useful in the prevention and treatment of breast cancer, prostate cancer and hepatocellular carcinoma (Sun et al, 1998 ; Khan et al, 2011 ; Chen J. et al, 2015 ; Youssef et al, 2016 ). In addition, biochanin A was shown to exert neuroprotective effect in neurodegenerative diseases via inhibiting microglia activation or attenuating L-glutamate cytotoxicity (Chen et al, 2007 ; Tan et al, 2013 ; Wang J. et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…We have made the new implementation freely available through the use of our new program CISNE (Code for the Identification of Synergism Numerically Efficient) 27 . Therefore, our new method keeps the generality of a theory that has been widely validated and applied to a variety of biological systems 28 , but, at the same time, it represents an improvement on the implementation of that theory. This is because it allows to determine accurately possible synergistic effects in biological systems within a wide range of characteristic parameters where the previous methods failed.…”
Section: Introductionmentioning
confidence: 99%
“…21 On the 8th day, the kunming mice were randomly assigned to four groups (12 animals per group): group 1 was administered a 5% glucose injection, group 2 was administered free brucine, group 3 was administered brucine liposomes and group 4 was administered NGR-brucine liposomes. The brucine formulations were all injected via the tail vein on days 8, 10, 12 and 14, at a dose of 15 mg/kg.…”
Section: In Vivo Antitumor Activitymentioning
confidence: 99%